Analisis Pengaruh Self-Efficay terhadap Kinerja Karyawan dengan Peran Motivasi kerja dan Keterikatan Karyawan sebagai Variabel Mediasi - Naufal, Muhammad Rizqullah (Universitas Tanjungpura, 2025)
Human Resources (HR) is a key element in an organization that is involved in various organizational activities and processes. Self-efficacy, work motivation, and employee engagement are important factors that are interrelated and can affect employee performance. This study aims to analyse the effect of self-efficacy on employee performance with work motivation and employee engagement as mediating variables. The population in this study were all administrative employees at the Politeknik Negeri Pontianak, totalling 167 people. The research method used is quantitative with Partial Least Squares Structural Equation Modelling (PLS-SEM) data analysis techniques. The results of the study show that (1) self-efficacy has a significant effect on employee performance (2) Self-Efficacy has a significant effect on Work Motivation (3) Self-Efficacy has a significant effect on Employee Engagement (4) Work Motivation has a significant effect on Employee Performance (5) Work Motivation has a significant effect on Employee Engagement (6) Employee Engagement has a significant effect on Employee Performance (7) Self-Efficacy has an indirect effect on Employee Performance through Work Motivation (8) Self-Efficacy has an indirect effect on Employee Performance through Employee Engagement.